Improvements in intensive care units - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
We have had some important improvements in the intensive care units (ICU) like high flow oxygen system (HFOS), therapeutic hypothermia, extra corporeal membrane oxygenation (ECMO), extra corporeal carbon dioxide removal (ECCOR), echocardiography (ECHO) and ultrasonography (US). HFOS gives oxygen to the patients at rates of flow higher (up to 60 L/min) than that delivered traditionally in LFOS (up to 16L/min). It is obtained 1 cmH2O PEEP for every 10L/min of flow delivered by HFOS. HFOS serves as an important alternative to noninvasive mechanical ventilation especially in the management of the patients with hypoxemic respiratory failure. Post-resuscitation care consists of optimization of oxygenation and ventilation, avoiding hypotension, treating immediate precipitants of cardiac arrest such as acute coronary ischemia and initiating therapeutic (induced) hypothermia. Therapeutic hypothermia decreases cerebral metabolic rate, blood volume, and intracranial pressure, prevents reperfusion injury. So hypotermia protects cerebral functions. ECMO, the type of cardiopulmonary support, has become an essential tool in critical care patients with severe respiratory and cardiac failure, refractory to conventional therapy methods. Critical care ultrasonography (CCUS) and echocardiography have utility for intensivist-performed, immediate diagnoses of life threatening diseases, with no need to transport patients to radiology or cardiology departments or wait for radiologist or cardiologist on a consultative basis. CCUS and echocardiography should be an essential part of training of every ICU physician.
Keywords: Intensive Care Units; Oxygen inhalation therapy; Extracorporeal membrane oxygenation; Extra corporeal carbon dioxide removal; Hypothermia; Induced; Echocardiography; Ultrasonography